A Dynamic Evaluation Method for High-Permeability New Energy Distribution Network Planning Considering Multistage Development Trends - Zhang, Junxiao; Gao, Chong; Wang, Tianlin; Duan, Yao; Xu, Min; Guo, Zuogang (Frontiers in Energy Research, 2022)
With the development of new power systems, high penetration of new energy (HPNE) will become a major feature of power systems in the future. In order to solve the problem that the traditional distribution network planning index makes it difficult to fully consider the impact of new energy access on the distribution network, this paper constructs a distribution network planning evaluation index system considering the characteristics of HPNE, and designs a set of static comprehensive evaluation methods of distribution network planning schemes based on the “over-average penalty” entropy weight method (EWM). At the same time, distribution network planning is a long-term dynamic process, and the static evaluation method makes it difficult to describe the actual situation of the multistage construction process of distribution networks. To this end, a dynamic evaluation method of distribution network planning is proposed, which realizes the comprehensive evaluation of multistage distribution network planning based on dual excitation control lines. Finally, an example of four 10 kV distribution network planning schemes of a power supply bureau are analyzed to prove the effectiveness of the proposed method.